SEP events and wake region lunar dust charging with grain radii. Issue 1 (1st January 2017) - Chandran, S.B. Rakesh; Rajesh, S.R.; Abraham, A.; Renuka, G.; Venugopal, Chandu
Abstract: Our lunar surface is exposed to all kinds of radiations from the Sun, since it lacks a global magnetic field. Like lunar surface, dust particles are also exposed to plasmas and UV radiation and, consequently they carry electrostatic charges. During Solar Energetic Particle events (SEPs) secondary electron emission plays a vital role in charging of lunar dusts. To study the lunar dust charging during SEPs on lunar wake region, we derived an expression for lunar dust potential and analysed how it varies with different electron temperatures and grain radii. Because of high energetic solar fluxes, secondary yield ( δ ) values reach up to 2.3 for 0.5 μm dust grain. We got maximum yield at an energy of 550 eV which is in well agreement with lunar sample experimental observation (Anderegg et al., 1972). It is observed that yield value increases with electron energy, reaches to a maximum value and then decreases. During SEPs heavier dust grains show larger yield values because of the geometry of the grains. On the wake region, the dust potential reaches up to −497 V for 0.5 μm dust grain. The electric field of these grains could present a significant threat to manned and unmanned missions to the Moon.